Responsible Research and Innovation Associated With Risk Communication and Public Engagement on Health Emergency Preparedness at the Local Level - Possenti, Valentina; De Mei, Barbara; Kurchatova, Anna; Green, Manfred; Drager, Kåre Harald; Villa, Roberta; d'Onofrio, Alberto; Saadatian-Elahi, Mitra; Moore, Vanessa; Brattekas, Kjersti; Karnaki, Pania; Beresniak, Ariel; et al. (Frontiers in Communication, 2022)
Responsible Research and Innovation (RRI) associated to public health emergency preparedness (PHEP) and response pose major challenges to scientific community and civil society, because a multistakeholder and interdisciplinary methodology is needed to foster public engagement. In 2017, within “Action plan on Science in Society related issues in Epidemics and Total pandemics”, twenty-three initiatives in eleven cities – Athens, Brussels, Bucharest, Dublin, Geneva, Haifa, Lyon, Milan, Oslo, Rome, Sofia – represented effective opportunities for Mobilisation and Mutual Learning on RRI issues in matter of PHEP with different community-level groups. These experiences show that to effectively address a discourse on RRI-related issues in PHEP it is necessary to engage local population and stakeholders, which is challenging because of needed competences and resources. Under the COVID-19 pandemic, we are proven that such a diversified multistakeholder engagement on RRI related to PHEP locally needs further elaboration and practical development.